UPAYA PENINGKATAN PENGETAHUAN TENTANG AKTIVITAS FISIK DAN ASUPAN GIZI SEIMBANG LANSIA DI MASA PANDEMI COVID-19 - Irma Mustika Sari; Eska Dwi Prajayanti (P3M Universitas Aisyiyah Surakarta, 2021)
Background ; The view of some people who consider the elderly as human beings who are incapable, weak, and sickly, causes all activities to be very limited. This condition is exacerbated by the absence of time, place, and opportunity for the elderly to carry out activities. The COVID-19 pandemic (coronavirus) causes many changes in daily life, this can also have an impact on the elderly considering that the body condition of the elderly is susceptible to being exposed to viruses and diseases if the immune system is not optimal. Method of Implementation ; Conduct health counseling to elderly posyandu cadres about balanced nutritional intake for the elderly during the covid-19 pandemic, and provide exercise videos to elderly posyandu cadres in the Kentigan Kulon area, Jebres sub-district, Surakarta with the hope that the video can be useful and can be used as sports and physical exercise for the elderly. Conclusion ; Â There is an increase in knowledge of elderly posyandu cadres after being given health counseling about balanced nutrition intake during the covid 19 pandemic. Routine physical exercise activities can increase body immunity during the pandemicÂ Keywords: Â Elderly, physical activity, balanced nutrition